Morphological development in the interlanguage of English learners of Xhosa - Hobson, Carol Bonnin (Rhodes University, Faculty of Humanities, Department of English Language and Linguistics, 2000)
This study investigates the development of morphology in the interlanguage of English learners of Xhosa. A quasi-longitudinal research design is used to trace development in the oral interlanguage of six learners of Xhosa for a period of eight months. The elicitation tasks employed range from fairly unstructured conversation tasks to highly structured sentence-manipulation tasks. The learners have varying levels of competence at the beginning of the study and they are exposed to input mainly in formal contexts of learning. One of the aims of the study is to investigate whether the features of interlanguage identified in other studies appear in the learner language in this study. Most other studies discussed in the literature have investigated the features of the interlanguage produced by learners of analytic and inflectional languages. However, this study analyses the interlanguage of learners of an agglutinative language. Studies of other languages have concluded that learners do not use inflectional or agreement morphology at early stages of development and this conclusion is tested for learners of an agglutinative language in this study. Since agreement and inflectional morphology play a central role in conveying meaning in Xhosa, it is found that learners use morphology from the beginning of the learning process. Although forms may be used incorrectly and the functions of forms may be restricted, morphemes appear in the interlanguage of learners of this study earlier than other studies predict. One of the characteristics of early interlanguage and an early form of learner language called the Basic Variety (Klein & Perdue 1997) is the lack of morphology, but this feature proves to be inadequate as a measure of early development in the interlanguage of learners of a language such as Xhosa. This study concludes, therefore, that the presence of morphology in the interlanguage of learners of Xhosa cannot be an indicator of advanced language development.
Keywords: Grammar, Comparative and general -- Morphology; Xhosa language -- Foreign speakers; Xhosa language -- Morphology